Hydro-depositary and hydro-transmitting properties of soddy-podzolic soils in the course of simulating the water transfer by physically-grounded models - E. V. Shein; E. B. Skvortsova; S. S. Panina; A. B. Umarova; K. A. Romanenko (Бюллетень Почвенного института им. В.В. Докучаева)
The results of field experiments conducted on the medium loamy agro soddy-podzolic soil showed that due to the hydraulic head of water at the soil surface the moisture movement occurs predominantly through migration ways that deteriorate the hydro-depositary properties of soils. The moisture movement was studied by a special method performed in two soil monoliths identical in size (42 cm in diameter and 60 cm high). The monolith walls were covered by a film, foamed and buried with the view of avoiding the lateral water loss. Both monoliths were simultaneously saturated with water: one of them was under a constant head of water in 5 cm, the other monolith was watered by fine-dispersed sprinkler without the formation of the water layer at the soil surface. The study was aimed at modeling the water movement under conditions of small headed infiltration and without the head of water as well as comparing the calculated and experimental data with the view of assessing the most adequate experimental provision of the model - the major hydrophysical characteristics obtained by empiric methods in the experiment or those calculated on the basis of hydrological constants and soil properties (pedo-transmitting functions). It seemed reasonable to establish that the experimental provision of the model can be shown in the following order: the use of regional pedo-transmitting functions provides better results as compared to the major hydrophysical characteristics, the latter being obtained by the method of tensiometers and capillarometers is better than the pedo-transmitting characteristics used the particle-size distribution as a predictor in Agrotool program (ROSETTA database) as well as those obtained by Voronin’s “secants”.